TiTaCN-Co Cermets Prepared by Mechanochemical Technique: Microstructure and Mechanical Properties. (2016) - Fides, Martin; Hvizdoš, Pavol; Balko, Ján; Chicardi, Ernesto; Gotor, Francisco J.
Abstract: Microstructure and mechanical characterization of (Ti, Ta)(C, N)-Co based solid solution cermets prepared by two mechanochemical synthesis processes (one- and two-step milling) and a pressureless sintering in protective helium atmosphere. Materials with composition of Tix Ta1-x C0.5 N0.5 -20%Co with two different Ti/Ta ratios (x = 0.9 and x = 0.95) were developed to prepare four groups of experimental materials. Microstructures were observed using confocal microscopy and grain size was evaluated using image analysis. Mechanical testing was carried out using nanoindentation equipment and nanohardness and indentation Young's modulus were obtained. Mechanical properties of individual phases were measured using single load/unload method with 20 mN maximum load (40 mN/min loading rate and maximum 10 s holding time for each indent). Mechanical properties of each material as a bulk were obtained also by single load/unload method with 300 mN maximum load (600 mN/min loading rate and maximum 10 s holding time). The resulting mechanical properties were comparable to that of typical industrial hardmetal cermets. Two-step milling resulted in finer microstructure but a wider range of grain size distribution. No significant dependence between mechanical properties and number of milling steps was found. However, the materials with higher amount of Ta showed slightly higher indentation elasticity modulus.